Variáveis condicionantes do processo de produção científica dos centros de recursos naturais da embrapa - Almir Martins Oliveira, José; Bressan, Matheus; de Vasconcelos Barros, Edgard; Norberto Muniz, José (Revista Ceres, 2025)
The aim of this work is describe scientific production at the natural resource centers of EMBRAPA, and, more specfically to search for the relationship between scientific productivity and some independent variables.